Characterization of Xe‐133 global atmospheric background: Implications for the International Monitoring System of the Comprehensive Nuclear‐Test‐Ban Treaty. Issue 9 (3rd May 2016) - Achim, Pascal; Generoso, Sylvia; Morin, Mireille; Gross, Philippe; Le Petit, Gilbert; Moulin, Christophe
Abstract: Monitoring atmospheric concentrations of radioxenons is relevant to provide evidence of atmospheric or underground nuclear weapon tests. However, when the design of the International Monitoring Network (IMS) of the Comprehensive Nuclear‐Test‐Ban Treaty (CTBT) was set up, the impact of industrial releases was not perceived. It is now well known that industrial radioxenon signature can interfere with that of nuclear tests. Therefore, there is a crucial need to characterize atmospheric distributions of radioxenons from industrial sources—the so‐called atmospheric background—in the frame of the CTBT. Two years of Xe‐133 atmospheric background have been simulated using 2013 and 2014 meteorological data together with the most comprehensive emission inventory of radiopharmaceutical facilities and nuclear power plants to date. Annual average simulated activity concentrations vary from 0.01 mBq/m 3 up to above 5 mBq/m 3 nearby major sources. Average measured and simulated concentrations agree on most of the IMS stations, which indicates that the main sources during the time frame are properly captured. Xe‐133 atmospheric background simulated at IMS stations turn out to be a complex combination of sources. Stations most impacted are in Europe and North America and can potentially detect Xe‐133 every day. Predicted occurrences of detections of atmospheric Xe‐133 show seasonal variations, more accentuated in the Northern Hemisphere, where the maximum occurs in winter. To our knowledge, this study presents the first global maps of Xe‐133 atmospheric background from industrial sources based on two years of simulation and is a first attempt to analyze its composition in terms of origin at IMS stations. Key Points: Simulation of two years of Xe‐133 atmospheric background from industrial releases worldwide Characterization of Xe‐133 atmospheric background origin at monitoring stations locations Implications for nuclear weapon test detections